(untitled) (REVISTA NODO, 2012)
The purpose of the article is to nominate the locality of Chapinero in Bogota as a creative and cultural district for the city. Firstly, four theoretical outlooks are referred to as conceptual framework (information societies, knowledge societies, creative economies and creative cities), in order to evaluate and validate each of their implications to the proposal. Then, Chapinero’s capacity as creative and cultural district in Bogota is analyzed from the point of view of the activities being held at the locality, as well as the industries established within its boundaries. Subsequently, the authors define the need to create one or more clusters to consolidate the proposal, and outline the directives to take into account to achieve it. Finally, it is concluded that the locality of Chapinero is endowed with great potential to become a creative and cultural district in Bogota, but it is up to both national and local government officials to make it true.